SUBSIDY POLICY ON NATURAL GAS AND COAL DEVELOPMENT - Sahat Aditua Fandhitya Silalahi (Pusbindiklat - LIPI, 2012)
Indonesian government had developed a policy to diversify energy from other sources in order to reduce thedependency towards fossil fuel. However, subsidy on fossil fuel impedes the efforts. Therefore, the governmentneeds to reallocate the subsidy in order to support the diversification. Indonesia still has vast amount of naturalgas and coal resources and they have opportunities to replace fossil fuel as the main energy. This paper aimsto study the opportunities to implement subsidy policy in developing those two energy sources. The study usesdescriptive-qualitative approach and uses secondary data from literature, journal, internet and other secondarysources. The study finds that there is an opportunity to implement subsidy for revitalizing the city gas program.This program should be able to replace liquefied petroleum gas. The government can also implement subsidy inorder to accelerate the coal liquefaction development.